Dicentric X isochromosomes in man. Issue 6 (December 1976) - Howell, R T; Roberts, S H; Beard, R J
Abstract : Four cases of Turner's syndrome are presented in which an apparent X isochromosome i(Xq) has been found to possess two regions of centromeric heterochromatin. It is suggested that these chromosomes were isodicentric structures capable of functioning as monocentric elements as a result of the inactivation of one centromere. The prevalence of mosaicism is believed to be a consequence of the dicentric nature of these chromosomes, and it is considered possible that a high proportion of X isochromosmes are structurally dicentric. Banding patterns showed that the exchange site involved in the formation of the dicentric chromosome was different in at least three of the cases.